2018
DOI: 10.3390/w10111584
|View full text |Cite
|
Sign up to set email alerts
|

A Modified Empirical Retracker for Lake Level Estimation Using Cryosat-2 SARin Data

Abstract: Satellite radar altimetry is an important technology for monitoring water levels, but issues related to waveform contamination restrict its use for rivers, narrow reservoirs, and small lakes. In this study, a novel and improved empirical retracker (ImpMWaPP) is presented that can derive stable inland lake levels from Cryosat-2 synthetic aperture radar interferometer (SARin) waveforms. The retracker can extract a robust reference level for each track to handle multi-peak waveforms. To validate the lake levels d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…The gradual shrinkage before 1999 and rapid expansion since 2000 at Memar Co were similar to most endorheic lakes on the TP (e.g., Lei et al, 2014). Many studies have shown that precipitation has increased significantly on the interior TP since the late 1990s (Yang et al, 2014;Treichler et al, 2019), which has led to the significant lake expansion (Lei et al, 2014). Between 1972 and 2018, the lake level and water storage of Memar Co increased by 10.4 ± 0.6 m and 1.62 ± 0.11 Gt (from 1.86 to 3.49 Gt), respectively.…”
Section: Impact Of the Meltwater On The Inter-annual Lake Level Changes In Memar Comentioning
confidence: 56%
See 1 more Smart Citation
“…The gradual shrinkage before 1999 and rapid expansion since 2000 at Memar Co were similar to most endorheic lakes on the TP (e.g., Lei et al, 2014). Many studies have shown that precipitation has increased significantly on the interior TP since the late 1990s (Yang et al, 2014;Treichler et al, 2019), which has led to the significant lake expansion (Lei et al, 2014). Between 1972 and 2018, the lake level and water storage of Memar Co increased by 10.4 ± 0.6 m and 1.62 ± 0.11 Gt (from 1.86 to 3.49 Gt), respectively.…”
Section: Impact Of the Meltwater On The Inter-annual Lake Level Changes In Memar Comentioning
confidence: 56%
“…ICESat altimetry data were processed after Li et al (2014) and were used to examine water level variations between 2003 and 2009. CryoSat-2 data were processed after Xue et al (2018) and were used to investigate water level variations between 2010 and 2018. Both lakes were observed by the ICESat satellite two or three times a year (Phan et al, 2012) and by the CryoSat-2 satellite every 2 or 3 months (Kleinherenbrink et al, 2015;Jiang et al, 2017).…”
Section: Satellite Observationmentioning
confidence: 99%
“…Lake boundaries were extracted in false color image by manual delineation using ArcGIS 9.2 software. ICESat and Cryosat-2 satellite altimetry data were used to detect lake level changes between 2003 and 2017 (Li et al, 2014;Xue et al, 2018). Memar Co was monitored by ICESat satellite twice a year (pre-monsoon and post monsoon seasons) between 2003 and 2009 (Phan et al, 2012;Zhang et al, 2011).…”
Section: Satellite Observationmentioning
confidence: 99%
“…Using synthetic aperture radar (SAR) technology, Cryosat-2, and Sentinel-3 can monitor inland water at a finer along-track resolution, and with interferometric SAR technologies, Cryosat-2 can determine the cross-track angle of arrival of the radar echoes [19], [20]. Although the data produced using these techniques improve the quality of observation points to some extent, there is still a problem of complex waveform pollution [4], [8], [21].…”
mentioning
confidence: 99%
“…Villadsen et al [8] developed a multiple waveform persistent peak (MWaPP) algorithm by assuming that one peak reflected by the inland water occurs in all waveforms, but other peaks reflected by other bright targets or off-nadir water bodies are less likely to be persistent, which could deal effectively with complex multipeak waveforms affected by land. Xue et al [4] focused on Cryosat-2 synthetic aperture radar interferometer (SARin) waveforms and developed an improved ImpMWaPP retracker using a robust statistical method to obtain a reference water level and identifying the water-surface signal of the waveform based on this reference water level, thereby improving the processing performance for multipeak waveforms. Huang et al [22] used an improved waveform retracking, called the TIC (50% Threshold and Ice-1 Combined algorithm) to derive water This work is licensed under a Creative Commons Attribution 4.0 License.…”
mentioning
confidence: 99%